2022
DOI: 10.1021/acsomega.1c06897
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Transformation of Liquid Metal Microspheres in Aqueous Solution Triggered by Growth of GaOOH

Abstract: Liquid metals (LMs) are playing an increasingly important role in the fields of flexible devices, electronics, and thermal management due to their low melting point and excellent thermal and electrical conductivity, and the transformation of LMs in deionized water has recently received much attention. In this paper, we investigate the transformation process of EGaIn microspheres in deionized water and propose a two-step process of microspherical transformation, whereby the microspheres are first deformed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Under heating or long time storage circumstance, EGaIn micro/nanodroplets produced by ultrasonication in water (Figure S10A−C) or organic solvents had been proved that these were tended to transform into nonconductive GaOOH lamellae or nanorods because of the chemical reaction of Ga, water, and oxygen, resulting in the low chemical stability. 18 In addition, EGaIn coating produced from micro/nanodroplets by filtration tended to yield cracks on substrates, which would be fatal in electronic applications. 39 Surprisingly, LMPs could be stored in water for more than one month and still formed stable LMPs after being removed from the water, thus generating conductive routes by mechanical sintering (Figure S10D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under heating or long time storage circumstance, EGaIn micro/nanodroplets produced by ultrasonication in water (Figure S10A−C) or organic solvents had been proved that these were tended to transform into nonconductive GaOOH lamellae or nanorods because of the chemical reaction of Ga, water, and oxygen, resulting in the low chemical stability. 18 In addition, EGaIn coating produced from micro/nanodroplets by filtration tended to yield cracks on substrates, which would be fatal in electronic applications. 39 Surprisingly, LMPs could be stored in water for more than one month and still formed stable LMPs after being removed from the water, thus generating conductive routes by mechanical sintering (Figure S10D).…”
Section: Resultsmentioning
confidence: 99%
“…However, these LMs' nanodroplets still lack enough oxidation resistance due to the active metal atoms on their dynamic surfaces, resulting in chemical instability in various solvents. 18 It has been demonstrated that LMs can be wetted on high surface energy substrates (e.g., Au, 23 Ag, 24,25 and Cu 26 ) and form metallic bonds that cling securely to the substrate. In addition, the hydrogen bonds between gallium oxide layer and polymethacrylate glue are vital for achieving outstanding adhesion on substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallium indium alloy (EGaIn), as one kind of liquid metal (LM) that has a melting point close to or below room temperature, [20][21][22] has been widely used in electronic devices, thermal management, soft robots, and biological devices due to its excellent electrical and thermal conductivity, 23,24 low melting point (15.6 1C), 25 and non-toxicity. 26 In addition, EGaIn can be prepared into EGaIn microspheres by ultrasonic dispersion, 27,28 which can be used as nanofillers. EGaIn microsphere fillers are different from other rigid nanofillers because they can adapt to the deformation of the polymer matrix, thus effectively toughening the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…However, since most of the photothermal fillers are inorganic rigid particles, which can have a large impact on the flexibility of the substrate of the actuator and can seriously decrease the response speed of the photoactuator. In contrast, a liquid metal (LM), as an emerging flexible material, combines the fluidity of liquid 13 with the electrical conductivity 14 and thermal conductivity 15 of metal. What's more, similar to gold nanocrystals 16 and silver nanocrystals, 17 LM particles have photothermal effects in the near-infrared (NIR) laser.…”
Section: Introductionmentioning
confidence: 99%